Effects of nutritional counseling on dietary patterns in patients with mild cognitive impairment: insights from the BrainFit-Nutrition study - Hanslian, Etienne; Dell’Oro, Melanie; Schiele, Julia K.; Kandil, Farid I.; Hasanbasic, Dzenita; Henn, Cirus; Graessel, Elmar; Scheuermann, Julia-Sophia; Scheerbaum, Petra; Michalsen, Andreas; Jeitler, Michael; Kessler, Christian S. (Frontiers in Nutrition, 2025)
IntroductionThis study examines the effects of a structured nutritional counseling intervention for individuals with mild cognitive impairment (MCI) via synchronized online courses conducted bi-weekly over six months.MethodsThis work presents a secondary analysis of the BrainFit-Nutrition study, which explored the impacts of both 1) dietary counseling interventions (comparing a Whole Food Plant-Based (WFPB) diet with a diet based on the German Nutrition Association guidelines or Deutsche Gesellschaft für Ernährung, DGE) and 2) standardized versus individualized computer-based cognitive training, within a 2x2 factorial randomized controlled trial design for participants with MCI. While the primary outcome of the BrainFit-Nutrition study assessed the impacts of diet and cognitive training on cognitive performance, this secondary data analysis focuses on dietary habits and their changes over time. Dietary behaviors in 261 participants (52.2% female), aged between 60 and 86 years, were monitored using food frequency questionnaires at baseline (t0), post-intervention (t6), and at a 12-months follow-up (t12). Short-term (t6) and long-term (t12) dietary pattern effects were analyzed by comparing consumption frequencies across various food categories between the dietary groups, employing ANCOVAs with baseline values (t0) as covariates for exploratory analysis.ResultsThroughout the intervention period, most participants in both groups maintained an omnivorous diet, with minimal shifts towards pescatarian, ovolacto-vegetarian, and vegan diets, especially in the WFPB group, which saw a minor increase in vegan and ovolacto-vegetarian participants by the end of the study. Across both dietary groups, vegetable, fruit, and whole grain consumption remained steady, with no notable intergroup differences. A decrease in meat, fish, and egg consumption was observed in both groups, with a more marked reduction in the WFPB group.DiscussionThese findings suggest that while targeted dietary interventions can foster healthier dietary patterns among MCI patients, the type of dietary choices may be less impactful for individuals with MCI than participation in dietary interventions in general. Further prospective research is warranted to clarify the potential benefits of dietary adjustments on cognitive health and to refine dietary guidance tailored to this specific population.